Pengaruh Keterampilan Dribbling Terhadap Kondisi Fisik (Daya Tahan Cardiovascular Vo2max) Pada Pemain Ekstrakurikuler Futsal Himajas Putra Semester I Di Universitas Dehasen Bengkulu - Hidayat, Arrahman; Sumantri, Ajis; Syahputra, Roni (Journal Of Dehasen Educational Review, 2025)
This study aims to determine how the Effect of Dribbling Skills on Physical Condition (Cardiovascular Endurance Vo2max) in Himajas Male Futsal Extracurricular Players Semester I at Dehasen University Bengkulu. This type of research is an experimental study with a sample of 28 players. The results of this study indicate that dribbling skills have an influence on cardiovascular endurance Vo2max in Himajas Male Futsal Extracurricular Players Semester I at Dehasen University Bengkulu. It is proven by the results of the difference test between the Pre-Test and Post-Test of Cardiovascular Vo2max Endurance resulting in a tcount value of 11.47 and a ttable value of 1.725. That means tcount > ttable, so it can be concluded that H0 is rejected and Ha is accepted, so it can be concluded that the results of the study between Pre-Test and Post-Test on Cardiovascular Vo2max Endurance there is a significant difference. Thus the hypothesis that reads ‘Dribbling skills have a significant effect on increasing Cardiovascular Vo2max Endurance’, is accepted. From the Pre-Test data, the average value is 35.38, then during the Post-Test the average value reaches 45.19. The change in the average value of Cardiovascular Vo2max Endurance can be seen from the difference in the average value of 9.81.